Der Opfermythos bei Elfriede Jelinek Eine historiografische Untersuchung - Paulischin-Hovdar, Sylvia (2017)
This paper presents a new, interdisciplinary method to adequately interpret Elfriede Jelinek's texts, integrating contemporary historical theories of fascism, national-socialism and the Austrian victim myth into the exemplary literary analysis.